Effect of Boundary Edge in DOPC/DPPC/Cholesterol Liposomes on Acceleration of l-Histidine Preferential Adsorption - Ishigami, Takaaki (Langmuir : the ACS journal of surfaces and colloids, 2016)
In order to investigate the interaction of hydrophilic molecules with liposomal membranes, we employed 1-(4-(trimethylamino)phenyl)-6-phenyl-1,3,5-hexatriene and 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine-N-(5-dimethylamino-1-naphthalenesulfonyl) as fluorescent probes to monitor the surface regions of the membrane, and the results for various liposomes were plotted in correlation diagrams. According to the formation of a variety of phase states, different tendencies of decreasing surface hydrophobicity were observed in the liposomes that were modified with high concentrations of cholesterol or in the liposomes that were composed of ternary components. These liposomes, with hydrophobic surfaces, also showed preferential adsorption of l-histidine (l-His), and the hydrophobicity of the liposomal membrane at the surface changed during l-His adsorption regardless of the initial liposomal properties. Furthermore, we revealed that accelerated adsorption of l-His and preferential binding was induced in ternary liposomes forming boundaries between two separate phases